2006
DOI: 10.1007/s10517-006-0124-1
|View full text |Cite
|
Sign up to set email alerts
|

Chronodromotropic coordination in cats

Abstract: The coordinated nervous influences on HR and atrioventricular conduction velocity (chronodromotropic coordination) were examined in wakeful cats. The wave structure and reflex reactions of RR and atrioventricular (AV) intervals to stress noise stimulation were studied under normal conditions and during the action of blockers of peripheral receptors in ANS. Variations of both intervals had similar wave structure (power spectrum) and similar reactions to noise stimulus. Atropine pronouncedly decreased all compon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
6
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 6 publications
2
6
0
Order By: Relevance
“…We found that pentobarbital had a similar effect on AV interval, causing its shortening and decrease in the ranges of all frequency bands. This, together with other data [1,2], indicates a close relationship between chronotropic and dromotropic nervous effects (chronodromotropic coordination). However, it does not mean that AV delay always changes strictly parallel to the period of cardiac contractions.…”
Section: Resultssupporting
confidence: 83%
See 3 more Smart Citations
“…We found that pentobarbital had a similar effect on AV interval, causing its shortening and decrease in the ranges of all frequency bands. This, together with other data [1,2], indicates a close relationship between chronotropic and dromotropic nervous effects (chronodromotropic coordination). However, it does not mean that AV delay always changes strictly parallel to the period of cardiac contractions.…”
Section: Resultssupporting
confidence: 83%
“…However, it does not mean that AV delay always changes strictly parallel to the period of cardiac contractions. It was previously shown that the same reflexogenic exposure can cause opposite reactions of RR and AV intervals [1] and that blockers of the autonomic nervous system peripheral receptors have different effects on the spectral characteristics of RR and AV intervals [2]. One more manifestation of the intricate chronodromotropic coordination is presumably the inversion of phase ratio of respiratory oscillations of RR and AV intervals detected in this study.…”
Section: Resultssupporting
confidence: 61%
See 2 more Smart Citations
“…At the same time, dromotropic, inotropic, and lusitropic effects are poorly studied. The ratio between various components of cardiac reflexes was estimated only in few studies [1][2][3][4].Here we evaluated the ratio between chronotropic and dromotropic components of various cardiac reflexes in cats. …”
mentioning
confidence: 99%